PEMBINAAN NARAPIDANA TIPIKOR DI LEMBAGA PEMASYARAKATAN - Samara, Finsensius; Winriyarti Silly , Amanda; N. Supadi , Fransiska; K. Soo, Yakobus; A. Pau , Fransiskus; U. Limu, Kristian (Gapenas Publisher, 2024)
This research aims to know the way of character building included heart learning, thought learning, sport learning, sense and worklearning, to know the problems of implementing character building program regarding heart learning, thought learning, sport learning, sense and work learning. This study used analytical descriptive qualitative. The result of this research shows that the inhibiting factors in character building development for corruptors are the lack of human resource in quality and quantity. The lack of human resources in quantity because the rasio of officers in correction department do not appropriate with the number of curruptors. In quantity, correction department does not have good human resource in supporting the character building of thought learning because it needs professional staffs. The efforts to solve the problems of implementing character building through human resource empowerment. Namely involving human resources who have an education background in the correction department Class IIA Kupang, both staff and inmates, to become coaches for other inmates, so that the coaching program does not stagnate and with the support of a third party